Allele-specific expression of a variant-specific surface protein (VSP) of Giardia lamblia. - Yang, Y (1994)
The surfaces of Giardia lamblia trophozoites demonstrate variable expression of a set of cysteine-rich surface proteins, called variant-specific surface proteins (VSP). The cloned Giardia line, WBA6, expresses a 170 kD VSP (VSPA6 or CRP170) which contains approximately 18 to 23 copies of a 65 amino acid repeat. We have cloned the expressed vspA6 gene containing 23 repeats from a genomic library as well as copies of the vspA6 gene with only 8 or 9 repeats from both WBA6 and from WB1269, a cloned line derived from WBA6 which has lost the expressed copy of the gene. The recombinant clones containing the genes with only 8 or 9 repeats have 8 nucleotide substitutions in the coding region. All the recombinant clones map to the same chromosomal location, yet RNA sequencing and comparison with the transcript size indicate that only the clone with 23 repeats contains a gene producing a stable transcript. The most likely interpretation of these data is that G.lamblia trophozoites contain multiple alleles of the vspA6 gene of which only one is expressed.